Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/jnr.490430105
|View full text |Cite
|
Sign up to set email alerts
|

OX‐40 antibody enhances for autoantigen specific Vβ8.2+ T cells within the spinal cord of lewis rats with autoimmune encephalomyelitis

Abstract: The V beta 8.2 T cell receptor (TCR) component is the predominant V beta gene product associated with antigen specific CD4+ T cell response to the major encephalitogenic epitope of myelin basic protein (MBP) in Lewis rats. Lewis rats were actively immunized with MBP in complete Freund's adjuvant and the V beta 8.2 positive and negative cells were analyzed for IFN-gamma mRNA production and OX-40 cell surface expression during the onset of EAE. The V beta 8.2+ T cells isolated from the spinal cord produced the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
(22 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, signaling through the CD134-CD134L pathway has been shown to reverse peripheral tolerance (45). CD134 ϩ T cells have also been associated with various autoimmune diseases (30,(32)(33)(34), and targeting of the CD134-CD134L pathway is believed to hold therapeutic potential in the treatment of autoimmunity and possibly in enhancing vaccine efficacy (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, signaling through the CD134-CD134L pathway has been shown to reverse peripheral tolerance (45). CD134 ϩ T cells have also been associated with various autoimmune diseases (30,(32)(33)(34), and targeting of the CD134-CD134L pathway is believed to hold therapeutic potential in the treatment of autoimmunity and possibly in enhancing vaccine efficacy (46).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo evidence has demonstrated that the CD134-CD134L interaction can provide a costimulatory signal to T cells, increasing T cell proliferation and cytokine production (25,26) as well as influencing B cell proliferation and Ig production (27,28). CD134 ϩ T cells have been implicated in various immune-mediated diseases, such as experimental autoimmune encephalomyelitis (29,30), rheumatoid arthritis (31,32), inflammatory skin disease (33), as well as graft-vs-host disease (34). In experimental autoimmune encephalomyelitis, administration of a neutralizing anti-CD134L mAb or OX40-Fc fusion protein ameliorates disease (35,36), while in animals lacking CD28 costimulation, CD134-CD134L blockade can completely abrogate disease (37).…”
Section: T Is Now Firmly Established That Costimulatory Signals Prmentioning
confidence: 99%
“…Lewis rats immunized with myelin basic protein and complete Freund's adjuvant, which develop the Th1-mediated autoimmune disease EAE, show an increase of CD134 ϩ cells in their lymph nodes. The majority of these cells express an autoreactive T cell receptor, but comprise only a very small part of the total lymphocyte population [40]. CD134 ϩ Th1-type cells were also shown to specifically invade the spinal cord in a passive form of EAE, induced by transfer of an encephalitogenic T cell line [19]; depletion of these cells prevented disease induction [16].…”
Section: Discussionmentioning
confidence: 99%
“…If as we predict, the OX-40R ϩ cells at the tumor site or draining lymph nodes are the tumor-specific T cells in vivo (27)(28)(29), then engagement of the OX-40R in vivo should lead to an enhanced antitumor-specific response. Therefore, we investigated whether engagement of the OX-40R in vivo during tumor priming would lead to an increase in tumor-free survival or a delay in tumor development.…”
Section: Ox-40r Engagement In Vivo During Tumor Priming (Sarcoma)mentioning
confidence: 92%
“…Approximately 15-40% of the T cells that invade the inflammatory tissue during an acute episode of autoimmune encephalomyelitis (an animal model for multiple sclerosis) are OX-40R ϩ , whereas 100% of the invading T cells express the IL-2R (25,27). Spinal cord T cells isolated from the CNS of rats with experimental autoimmune encephalomyelitis (EAE), sorted based on OX-40R expression, had their TCR CDR3 regions (Ag-binding region) sequenced.…”
mentioning
confidence: 99%